2013
DOI: 10.1186/1752-153x-7-131
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the major constituents in Chinese medicinal preparation SuoQuan formulae by ultra fast high performance liquid chromatography/quadrupole tandem mass spectrometry

Abstract: BackgroundThe SuoQuan formulae containing Fructus Alpiniae Oxyphyllae has been used to combat the urinary incontinence symptoms including frequency, urgency and nocturia for hundreds of years in China. However, the chemical information was not well characterized. The quality control marker constituent only focused on one single compound in the current Chinese Pharmacopeia. Hence it is prudent to identify and quantify the main constituents in this herbal product. This study aimed to analyze the main constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…On the basis of TCM theory, these two herbs were commonly combined for use as urine astringent and for warming the kidneys and were also commonly prescribed by TCM physicians for BPH. Meanwhile, recent studies have reported on the quantitative analysis of their major constituents 17 and the resulting improvement of renal function. 18 Fu Pen Zi ( Fructus Rubi ) was among the commonly prescribed single herbs for BPH patients in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of TCM theory, these two herbs were commonly combined for use as urine astringent and for warming the kidneys and were also commonly prescribed by TCM physicians for BPH. Meanwhile, recent studies have reported on the quantitative analysis of their major constituents 17 and the resulting improvement of renal function. 18 Fu Pen Zi ( Fructus Rubi ) was among the commonly prescribed single herbs for BPH patients in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Radix linderaeis used to regulate Qi (Kim & Pham, ). Meanwhile, Radix linderae can effectively alleviate inflammation (Chen et al ., ). Rhizoma Corydalis may be useful to alleviate neuropathic pain (Choi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Chemical profiling applies advanced analytical instrumentation to study the chemical content of a single plant Chen et al, 2012;Li et al, 2014;Hou et al, 2014;Cui et al, 2012;Xu et al, 2013;Gao et al, 2013;Chen et al, 2013;Tao et al, 2013), as well as to determine the pharmacology and toxicology profile of herbs (Kim et al, 2014;Blacksell et al, 2014;Hao and Xiao, 2014). Profiling is a method in which a set of criteria is used to determine a characteristic of a single herbal product.…”
Section: Standardization Of Health (Functional) Food Productsmentioning
confidence: 99%